Amphiphilic diselenide-containing supramolecular polymers. Issue 5 (13th November 2014) - Tan, Xinxin; Yang, Liulin; Huang, Zehuan; Yu, Ying; Wang, Zhiqiang; Zhang, Xi
Abstract : This communication describes the fabrication of diselenide-containing supramolecular polymers. Abstract : This communication describes the fabrication of diselenide-containing supramolecular polymers. The diselenide-containing supramolecular polymers were fabricated by equimolarly mixing (FGGC11Se)2 and CB[8] in aqueous solution driven by host–guest interactions between cucurbit[8]uril (CB[8]) and Phe-Gly-Gly. The amphiphilic diselenide-containing supramolecular polymers could further form aggregates for loading hydrophobic small molecules such as Nile Red and releasing them upon addition of oxidants or reductants. This line of research not only expands the library of selenium-containing polymers, but also offers a new strategy to develop functional supramolecular polymers for drug delivery.